Analysis of the Learning Process of Computer Programming Logic in an 8-Year-Old Elementary School Student at Home through the Scratch Program - García, Victor (Digital, 2024)
This paper presents a study guide and an analysis of its use in the computer programming learning process of an 8-year-old elementary school student through the Scratch program. The research’s objective is to explore and understand how this individual student approaches learning programming skills and tackles challenges within the Scratch environment. An individual case study approach was adopted at home, combining qualitative and quantitative methods to gain a comprehensive insight into the student’s learning process. The study was conducted without grant support, and the researcher actively participated as an educator and observer in the student’s learning sessions. Performance was assessed, and a semi-structured interview was conducted to inquire about the student’s experiences, motivations, and interests regarding programming in Scratch, as well as their feelings after the training. Additionally, the student’s activities during programming sessions were meticulously recorded, and projects created in Scratch were analyzed to assess progress and understanding of concepts. The findings of this research have the potential to contribute to the field of programming education and provide valuable insights into how young elementary school-aged individuals can acquire computer and programming skills in an interactive environment such as Scratch. The results obtained demonstrate that using the proposed guide to introduce elementary school students to programming at home, with parents acting as educators, is feasible. Therefore, it helps facilitate access to this knowledge, which is currently limited for many individuals in an official educational setting.